Development of Jatropha fruit shelling machine for kernel recovery in biodiesel production - Lim, Bo Yuan (2016)
Most of available shelling machines remove outer shells of Jatropha fruits to produce seeds, without removing husks (outer coating of seeds). The presence of the husks will affect oil yield and quality during oil extraction process in biodiesel production.Therefore, the project has developed a Multistage Jatropha Fruit Shelling Machine which is capable to produce oil-rich kernels (nucleus) by removing both of shells and husks from Jatropha fruits. The developed machine consists of two cracking units with screw-type rollers (rollers with male threads) and three separators (two blowers and a vibratory sieve). The designed screw-type rollers were found to be able to reduce breakage of kernels and kernel loss during separation process through blower. During performance evaluation, the roller clearance, blower air speeds and Jatropha fruits’ moisture content were found could significantly affect the machine performance. Based on the findings, the machine could remove 99.45 % of shells and 52.84 % of husks while controlling the kernel loss at 5.24 %. Further, the study has carried out Computational Fluid Dynamics (CFD) multiphase modeling of separation process through blower to understand dynamic behaviour of Jatropha fruits’ particles under airstreams. For the modeling, Dense Discrete Phase model (DDPM) under Eulerian framework in ANSYS Fluent software was selected to define particle injections following Rosin Rammler particle size distribution. The shape of particles was identified using Matlab Image Region Analyzer and the calculated aspect ratio, 0.625 was used to define non-spherical drag law. The numerical results show that the particles tend to flow in such a way to follow the direction of diverted air flow and vortices in separator duct with slope end design. The phenomena have a tendency to cause particle momentum loss especially for heavier kernel particles, causing the kernel particles to drop in the separator and leading to lower kernel loss during separation process. Furthermore, a scaling factor was developed based on dimensional analysis.The developed scaling factor suggests that the air airflow rate should be controlled to keep air velocity to be a constant parameter in order to ensure similar working condition in scale-up unit. In fact, the research project has successfully developed a more efficient shelling machine for kernel recovery and provided validated numerical model and scaling factor as better insights for making decision during development of future commercial unit that benefits Jatropha biodiesel industry.